2020
DOI: 10.1128/jvi.00470-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SUMO-SIM Interaction on the ICP0-Mediated Degradation of PML Isoform II and Its Associated Proteins in Herpes Simplex Virus 1 Infection

Abstract: ND10 nuclear bodies, as part of the intrinsic defenses, impose repression on incoming DNA. Infected cell protein 0 (ICP0), an E3 ubiquitin ligase of herpes simplex virus 1 (HSV-1), can derepress viral genes by degrading ND10 organizers to disrupt ND10. These events are part of the initial tug of war between HSV-1 and host, which determines the ultimate outcome of infection. Previously, we reported that ICP0 differentially recognizes promyelocytic leukemia (PML) isoforms. ICP0 depends on a SUMO-interaction moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Their findings indicate that three post-translational modifications, namely, ubiquitination, SUMOylation and phosphorylation, were involved in an unprecedented crosstalk in the ICP0 s degradation of PML [74]. In another study, Fada and colleagues reported that a PML II mutant lacking both lysine SUMOylation and SIM rendered it unrecognizable by ICP0, preventing ICP0-mediated degradation while still maintaining PML II localization to ND10 [75]. Moreover, it was observed that SP100 degradation was delayed in PML-/-infected cells and that the accumulation of ICP0 was reduced at low but not high multiplication of infection [76].…”
Section: Interplay Of Hsv-1 and Host Pml Proteinmentioning
confidence: 99%
“…Their findings indicate that three post-translational modifications, namely, ubiquitination, SUMOylation and phosphorylation, were involved in an unprecedented crosstalk in the ICP0 s degradation of PML [74]. In another study, Fada and colleagues reported that a PML II mutant lacking both lysine SUMOylation and SIM rendered it unrecognizable by ICP0, preventing ICP0-mediated degradation while still maintaining PML II localization to ND10 [75]. Moreover, it was observed that SP100 degradation was delayed in PML-/-infected cells and that the accumulation of ICP0 was reduced at low but not high multiplication of infection [76].…”
Section: Interplay Of Hsv-1 and Host Pml Proteinmentioning
confidence: 99%
“…They both contain a conserved RING-finger region but differ tremendously in the sequence of the RING domain and temporal expression ( Everett et al, 2010 ; Li et al, 2014 ). ICP0 is an immediate-early gene and known to play a critical role in innate immunity evasion, mostly by degrading a wide range of proteins involved in intrinsic and innate immunity, such as PML, DNA-PKcs, and IFI16 ( Lees-Miller et al, 1996 ; Orzalli et al, 2012 ; Jan Fada et al, 2020 ). In comparison, the study on EP0 mediated host protein degradation is very limited.…”
Section: Immune Evasion Mechanisms Of Pseudorabies Virusmentioning
confidence: 99%
“…Both knockdown methods targeted all PML isoforms at the common N-terminus but by different sequences. It has been reported that different PML isoforms are known to be recognized and degraded by ICP0 via totally distinct biochemical mechanisms [ 83 , 95 , 96 ]. Gu and colleagues showed that in HSV-1 infected cells, a single SIM located at ICP0 residues 362-364 was essential for the degradation of PML isoforms II, IV, and VI.…”
Section: Dual Role Of Nd10 In α-Herpesvirus Infectionmentioning
confidence: 99%
“…However, for the degradation of PML I, this SIM was found dispensable. Instead, PML I-interaction domains located within ICP0 residues 1–83 and 245–474 redundantly facilitate the interaction between ICP0 and PML and the degradation of PML I [ 95 , 96 ]. The obvious differential recognition of PML isoforms by ICP0 suggests that PML isoforms may play distinctive roles in HSV-1 infection.…”
Section: Dual Role Of Nd10 In α-Herpesvirus Infectionmentioning
confidence: 99%